Numerical evaluation for optimal design of number and positions of controllers in 2D frames under earthquake and wind loadings using different active control algorithms - Mehdipourpicha, Zabihollah (2012)
Documentos apresentados no âmbito do reconhecimento de graus e diplomas estrangeiros